2010
DOI: 10.1177/0741932510362507
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Peer Tutoring With Audio Prompting on Vocabulary Acquisition for Struggling Readers

Abstract: Reciprocal peer tutoring can be an effective supplement to teacher-led instruction, but students need to have the tutoring skills necessary to teach their peers successfully. Previous studies have addressed the challenge of providing essential information to a naïve tutor, allowing for correct modeling and feedback. The present study compared incidental learning of vocabulary words through classroom reading instruction to a combination of incidental learning supplemented with peer tutoring. Eight fourth-grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
1
7
1
Order By: Relevance
“…Most participants in the current study reported that peer teaching helped them develop their vocabulary ability faster and more easily. This is in line with various studies that peer teaching increases the students' knowledge of vocabulary acquisition (Kourea, Cartledge, & Musti-Rao, 2007), and peer teaching facilitates students to successfully master new English vocabulary words and their spellings (Greenwood, Arreaga-Mayer, Utley, Gavin, & Terry, 2001;Mackiewicz, Wood, Cooke, & Mazzotti, 2010). Since peer teaching requires students to use social skills and collaboration, students have more chances to interact with each other.…”
Section: Peer Teaching Techniques Peer Teaching Techniques Help Studesupporting
confidence: 84%
See 1 more Smart Citation
“…Most participants in the current study reported that peer teaching helped them develop their vocabulary ability faster and more easily. This is in line with various studies that peer teaching increases the students' knowledge of vocabulary acquisition (Kourea, Cartledge, & Musti-Rao, 2007), and peer teaching facilitates students to successfully master new English vocabulary words and their spellings (Greenwood, Arreaga-Mayer, Utley, Gavin, & Terry, 2001;Mackiewicz, Wood, Cooke, & Mazzotti, 2010). Since peer teaching requires students to use social skills and collaboration, students have more chances to interact with each other.…”
Section: Peer Teaching Techniques Peer Teaching Techniques Help Studesupporting
confidence: 84%
“…In the teaching of English vocabulary, peer teaching deems beneficial impacts. Mackiewicz, Wood, Cooke, and Mazzotti (2010) reported that peer teaching allowed learners to use new vocabulary socially in class, and the practice using new words in conversational contexts with peers and teachers, with whom the students felt acquainted, reinforced comprehension and increased learning relaxation.…”
Section: Peer Teachingmentioning
confidence: 99%
“…An image is usually presented with the voice-output device (e.g., miniature audio recorder, talking photo album) or a computer (see Wood et al, 2007). A few studies have explored the effect of AP used by a naïve educator to provide modeling and feedback to teach vocabulary to young students (Cooke, Mackiewicz, Wood, & Helf, 2009; Mackiewicz, Wood, Cooke, & Mazzotti, 2011). Cooke et al (2009) examined the effect of AP used by mothers and 4- to 5-year-old children, both with limited English proficiency.…”
Section: Apmentioning
confidence: 99%
“…Children generalized from pictures to real objects. AP with reciprocal tutor feedback has also been used to increase the accuracy of sight words in kindergarteners (Van Norman & Wood, 2008) and to improve vocabulary with peer tutoring for 9- to 11-year-old students (Mackiewicz et al, 2011). AP can be used with a computer or tablet, making it readily available, inexpensive, practical, and easy to use.…”
Section: Apmentioning
confidence: 99%
“…The inclusion of students with SEND calls for far more than simply placing the child in a mainstream classroom. Teachers should provide the necessary and targeted support based on child's individual needs for an adequate and complete educational experience (Burks, 2004;Cervantes, Lieberman, Magnesio, & Wood, 2013;Mackiewicz, Wood, Cooke, & Mazzotti, 2011). Various approaches have evolved recently holding the potential of aiding teachers to meet the diverse needs of their students in inclusive classrooms, such as cooperative learning instructional strategies, like peer tutoring.…”
Section: Peer Tutoring As An Inclusive Practicementioning
confidence: 99%